PENGARUH METODE PEMBELAJARAN KOOPERATIF DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA - WARMANSYAH, JHONI (Jurnal Pendidikan Usia Dini, 2016)
The aim of this research is to understand the effect of cooperative learning methods andlearning motivation toward mathematics learning outcomes. This research was conducted in SDNGunung Batu 2 and SDN Purbasari 1 second semester of academic year 2015/2016, usingexperimental methods to design treatment by level 2 x 2 involving 44 samples. The technique ofdata analysis in this research is using Anova Two Paths to see the main effects and interactions,then using Tukey's test to see modest effects. 1) The results of students' learning mathematics istaught through learning methods TGT higher than students taught by NHT method. (F count =14,50 > F table (Î± = 0.05) = 4,08). 2) There is an interaction effect between teaching methods andlearning motivation toward mathematics learning outcomes (F count = 19,15 > F table (Î± = 0.05)= 4,08). 3) At the students who have high motivation to learn, learning outcomes mathematicsgiven by the method TGT higher than students who are given the method NHT (F count = 20,82>F table (Î± = 0.05) = 3,11), and 4) In the students who have the motivation low learning,mathematics learning outcomes given the TGT method is lower than the students who are giventhe method NHT (F count = -1,05> F table (Î± = 0.05) = 3,11).